Nexus between government debt, economic policy uncertainty, government spending, and governmental effectiveness in BRIC nations: Evidence for linear and nonlinear assessments - Ma, Ru; Qamruzzaman, Md (Frontiers in Environmental Science, 2022)
Quality institutions augment economic sustainability by ensuring domestic resource optimization with equitable development principles. Therefore, ensuring this equitable development and quality institutions is required. This study assessed the effects of government debt, uncertainty of economic policies, and government spending on institutional quality, as measured by governmental effectiveness in BRIC (Brazil, Russia, India, and China) nations from1990–2020. This study applied several econometrical techniques for empirical nexus assessment, including Augmented ARDL, nonlinear Autoregressive Distributed Lagged (ARDL), and Fourier Toda-Yamamoto causality tests. This study documented long-run cointegration in both symmetry and asymmetric assessments. In the long run, both government debt and uncertain economic policies were significantly negatively associated with institutional quality, while government spending and institutional quality were positively associated. Furthermore, the results of asymmetric ARDL revealed both long- and short-run asymmetric relationships between institutional quality and government debt, EPU, and government spending. The directional causality test documented bidirectional causality between debt and institutional quality in all nations, whereas mixed causalities were detected for uncertain economic policy, institutional quality, and government spending. Regarding policy, the results of this study suggested that economic stability was indispensable for efficient institutional quality in BRIC nations.